Does laminar flow ventilation reduce the rate of infection? an observational study of trauma in England. - Pinder,EM; Bottle,A; Aylin,P; Loeffler,MD (Bone and Joint Journal, 2016)
AIMS: To determine whether there is any difference in infection rate at 90 days between trauma operations performed in laminar flow and plenum ventilation, and whether infection risk is altered following the installation of laminar flow (LF). PATIENTS AND METHODS: We assessed the impact of plenum ventilation (PV) and LF on the rate of infection for patients undergoing orthopaedic trauma operations. All NHS hospitals in England with a trauma theatre(s) were contacted to identify the ventilation system which was used between April 2008 and March 2013 in the following categories: always LF, never LF, installed LF during study period (subdivided: before, during and after installation) and unknown. For each operation, age, gender, comorbidity, socio-economic deprivation, number of previous trauma operations and surgical site infection within 90 days (SSI90) were extracted from England's national hospital administrative Hospital Episode Statistics database. Crude and adjusted odds ratios (OR) were used to compare ventilation groups using hierarchical logistic regression. Subanalysis was performed for hip hemiarthroplasties. RESULTS: A total of 803 065 trauma operations were performed during this time; 19 hospitals installed LF, 124 already had LF, 13 had PV and the type of ventilation was unknown in 28. Patient characteristics were similar between the groups. The rate of SSI90 was similar for always LF and PV (2.7% and 2.4%). For hemiarthroplasties of the hip, the rates of SSI90 were significantly higher for LF compared with PV (3.8% and 2.6%, OR 1.45, p = 0·001). Hospitals installing LF did not see any statistically significant change in the rate of SSI90. CONCLUSION: The results of this observational study imply that infection rate is similar when orthopaedic trauma surgery is performed in LF and PV, and is unchanged by installing LF in a previously PV theatre. Cite this article: Bone Joint J 2016;98-B:1262-9.